Home » Cauchy-Schwarz

Tag: Cauchy-Schwarz

Prove the pth power mean is less than the (2p)th power mean

We recall the definition of the pth power mean M_p.

For x_1, \ldots, x_n \in \mathbb{R}_{>0}, and p \in \mathbb{Z} with p \neq 0, we define the pth power-mean M_p as:

    \[ M_p = \left( \frac{x_1^p + \cdots + x_n^p}{n} \right)^{1/p}. \]

Now, for p > 0, prove M_p < M_{2p} for x_1, \ldots, x_n not all equal.


Proof. From the Cauchy-Schwarz inequality we know that for real numbers a_1, \ldots, a_n and b_1, \ldots, b_n, we have

    \[ \left( \sum_{k=1}^n a_k b_k \right)^2 \leq \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n b_k^2 \right) \]

with equality if and only if there is some y \in \mathbb{R} such that a_k y + b_k = 0 for all k. Letting a_k = x_k^p and b_k = 1 we have

    \[ \left( \sum_{k=1}^n x_k^p \cdot 1 \right)^2 < \left( \sum_{k=1}^n x_k^{2p} \right) \left( \sum_{k=1}^n 1 \right). \]

This inequality is strict since if equality held there would exist some y \in \mathbb{R} such that (x_k^p)y + 1 = 0 for all k, but this would imply x_k = \left(-\frac{1}{p} \right)^{1/p} for all k, contradicting our assumption that the x_k are not all equal. Since \sum_{k=1}^n 1 = n (see here), this implies

    \begin{align*}  &&\sum_{k=1}^n x_k^p &< \left( \sum_{k=1}^n x_k^{2p} \right)^{1/2} n^{1/2} \\ \implies && \left( \sum_{k=1}^n x_k^p \right)^{1/p} &< \left( \sum_{k=1}^n x_k^{2p} \right)^{1/2p} \cdot n^{1/2p}  &(\text{raising to } 1/p)\\ \implies && \left (\frac{1}{n} \right)^{1/p} \cdot \left( \sum_{k=1}^n x_k^p \right)^{1/p} &< \left( \sum_{k=1}^n x_k^{2p} \right)^{1/2p} \cdot \left( \frac{1}{n} \right)^{1/2p} & (\text{multiplying by } (1/n)^{1/p})\\ \implies && \left( \frac{\sum_{k=1}^n x_k^p}{n} \right)^{1/p} &< \left( \frac{\sum_{k=1}^n x_k^{2p}}{n} \right)^{1/2p} & (\text{combining terms})\\ \implies && M_p &< M_{2p}. \qquad \blacksquare \end{align*}

Prove an if and only if condition for equality in the Cauchy-Schwarz inequality

Recall the Cauchy-Schwarz inequality,

For arbitrary real numbers a_1, \ldots, a_n and b_1, \ldots, b_n we have

    \[ \left( \sum_{k=1}^n a_k b_k \right)^2 \leq \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n b_k^2 \right) \]

The claim is then that the equality sign holds if and only if there is a real number x such that a_k x + b = 0 for each k =1, \ldots, n.


Proof. (\Rightarrow) If a_k = 0 for all k, then equality clearly holds. Assume then that a_k \neq 0 for at least one k.

    \[ \left( \sum_{k=1}^n a_k b_k \right)^2 = \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n b_k^2 \right). \]

Then, considering the equation \sum_{k=1}^n (a_k x + b_k)^2 \geq 0 and defining,

    \[ A = \sum_{k=1}^n a_k^2, \qquad B = \sum_{k=1}^n b_k a_k, \qquad C = \sum_{k=1}^n b_k^2. \]

We have,

    \[ Ax^2 + 2Bx + C \geq 0 \ \implies \ x = \frac{-2B \pm \sqrt{4B^2 - 4AC}}{2A} = \frac{-B \pm \sqrt{B^2 - AC}}{A}. \]

But, since we know B^2 = AC (by assumption), we have x = -\frac{B}{A} which is in \mathbb{R} (since A \neq 0 since a_k \neq 0 for at least one k and each term a_k^2 in nonnegative, so the sum is strictly positive).
(\Leftarrow) Assume there exists x \in \mathbb{R} such that a_k x + b_k =0 for each k =1, \ldots, n. Then, a_k x + b_k = 0 \implies b_k = (-x)a_k. So,

    \begin{align*}  \left( \sum_{k=1}^n a_k b_k \right)^2 &= \left( -x \left(\sum_{k=1}^n a_k^2 \right) \right)^2 \\ &= x^2 \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n a_k^2 \right) \\ &= \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n x^2 a_k^2 \right) \\ &= \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n (-xa_k)^2 \right) \\ &= \left( \sum_{k=1}^n a_k^2 \right) \left( \sum_{k=1}^n b_k^2 \right). \qquad \blacksquare \end{align*}